#DefendPressFreedom: Paradigm Repair, Role Perceptions and Filipino Journalists' Counterstrategies to Anti-Media Populism and Delegitimizing Threats. (10th December 2022) - Macaraig, Ayee; Hameleers, Michael
ABSTRACT : Journalists increasingly have to cope with severe attacks – ranging from Fake News accusations to violence and death threats. To better understand how journalists can counter delegitimizing attacks such as anti-media populism and online harassment, this study examines their paradigm repair strategies to ward off assaults in the unconsolidated democracy of the Philippines. Through in-depth semi-structured interviews with 18 Filipino reporters and editors from three influential media outlets that then President Rodrigo Duterte targeted as enemies – the broadcaster ABS-CBN, the newspaper Philippine Daily Inquirer, and the website Rappler – this paper offers novel insights on journalists' counterstrategies with appeals to their strengthened roles as watchdogs, interpreters and disseminators of populist communication. Findings indicate that journalists discard practices like false equivalence and shift roles including from being detached observers to media freedom advocates and truth activists to respond to institutional attacks, rising disinformation, and perceived democratic erosion as they seek to speak truth to a populist in power. The study provides theoretical and empirical contributions by combining paradigm repair and role perceptions as tools in analyzing journalists' responses to legitimacy threats, and by presenting an understudied case of anti-media populism in the Global South.